The Strategy of Muhammadiyah Disaster Management Center (MDMC) in Forming Disaster Resilience Community in Kudus Regency - Nuril Maghfirah; Umi Qodarsasi; Ikhsan abdul Wahid (JURNAL PENELITIAN, 2025)
Kudus Regency - one of the regencies in Central Java Province, is a disaster-prone area and is located at the center of the economy. With this potential, the Muhammadiyah Disaster Management Center (MDMC) Kudus Regency has an important role starting from pre-disaster, during a disaster, and post-disaster. To build disaster resilience, community participation is needed, because the community is the front guard when a disaster occurs. This article aims to analyze how MDMC builds a disaster resilient community in Kudus Regency. This research is qualitative-descriptive research. Primary data in this research was obtained through in-depth interviews with the Chair of the Kudus Regency MDMC and the Coordinator of the Disaster Resilience Congregation. Meanwhile secondary data was obtained through books, journals and internet sources related to the topic. The results of this research are: 1) MDMC Kudus forms disaster resilient volunteers as a driving force for community disaster resilience; 2) MDMC Kudus maximizes social capital and human capital in forming a disaster resilient society.